Corporate Finance - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book comprises 19 papers published in the Special Issue entitled "Corporate Finance", focused on capital structure (Kedzior et al., 2020; Ntoung et al., 2020; Vintilă et al., 2019), dividend policy (Dragotă and Delcea, 2019; Pinto and Rastogi, 2019) and open-market share repurchase announcements (Ding et al., 2020), risk management (Chen et al., 2020; Nguyen Thanh, 2019; Štefko et al., 2020), financial reporting (Fossung et al., 2020), corporate brand and innovation (Barros et al., 2020; Błach et al., 2020), and corporate governance (Aluchna and Kuszewski, 2020; Dragotă et al.,2020; Gruszczyński, 2020; Kjærland et al., 2020; Koji et al., 2020; Lukason and Camacho-Miñano, 2020; Rashid Khan et al., 2020). It covers a broad range of companies worldwide (Cameroon, China, Estonia, India, Japan, Norway, Poland, Romania, Slovakia, Spain, United States, Vietnam), as well as various industries (heat supply, high-tech, manufacturing).